Pikeperch (Sander lucioperca) larval rearing optimization: utilization of lactic acid bacteria for improving microbiome diversity and digestive enzyme activity - Yanes-Roca, Carlos; Novakova, Eva; Leclercq, Eric; Vesely, Lukas; Galindo, A.; Pérez, J. A.; Penka, Tomas; Policar, Tomas (Frontiers in Marine Science, 2024)
Lactic acid bacteria (LAB) probiotics were evaluated for their impact on the microbiota and development of pikeperch (Sander lucioperca) larvae during their initial feeding stage (first 21 days). Pikeperch larvae were exposed to LAB probiotics in two ways: (1) via the live-feed only (Treatment 1, live-feed) or (2) via the live-feed and the larval culture water (Treatment 2, probiotic) in comparison to a control group without LAB supplementation. Total length (TL), myomere height (MH), and survival rate were significantly increased in the probiotic compared the Control group. The administration of probiotics significantly positively influenced the microbiome’s diversity. Specifically, the relative abundance of Cytophagales decreased and that of several other taxa increased in both probiotic treatments although differences between treatments became statistically insignificant by day 21. Furthermore, the different treatments had distinct and significant impacts on digestive enzyme development such as protease and lipase, with the most prominent differences occurring at seven days post-hatching (dph). Taken together, these results indicate that the use of LAB in both the live-feed and rearing water has a positive impact on the larvae microbiota and digestive enzyme development in turn positively impacting their development and viability under intensive rearing conditions.